A COMPREHENSIVE STUDY ON INTEGRATED OPTIMIZATION OF FLEXIBLE MANUFACTURING SYSTEM LAYOUT AND SCHEDULING FOR NYLON COMPONENTS PRODUCTION: A study on the integrated optimization of the FMS layout and schedule scheme for production of nylon components - Zhu, Cheng-Shun; Sun, Gaofeng; Yang, Kaihang; Huang, Yujun; Cheng, Dejun; Zhao, Qianhong; Zhang, Hui; Fang, Xifeng (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This study proposes an integrated optimization approach to the layout and scheduling of a hybrid-flow flexible manufacturing system to produce nylon components. The approach minimizes energy consumption and makespan simultaneously. In this approach, a flexible hybrid-flow manufacturing system for the layout and scheduling of nylon components production is established via traditional hybrid-flow shop scheduling based on the loading sequence, machine number, machine type, distance between two machines, multiple buffers, and robot manipulator transport. The traditional non-dominated sorting genetic algorithm II and improved multi-population NSGA-II were compared to obtain the best layout and scheduling to minimize energy consumption and makespan under various impact factors. The improved multi-population NSGA-II leads to optimizing the hybrid flow FMS layout and schedule according to the influencing factors. The energy consumption and makespan predictions are consistent with experimental observations. A case study was used to demonstrate and validate the proposed approach.